Kecanduan Media Sosial pada Remaja Akibat Pandemi Covid-19: Scoping Review - Iwan Shalahuddin; Ai Wia; Taty Hernawaty (Universitas Malahayati Lampung, 2023)
ABSTRACT The Covid-19 pandemic has significantly changed almost every aspect of life, including daily community activities such as school, work and worship which must now be done online. Social media has become one of the most widely used communication equipment during the Covid-19 pandemic. This condition will undeniably result in an increase in social media use and form social media addiction during the Covid-19 pandemic. The purpose of this study to identify a picture of social media addiction in adolescents due to the Covid-19 pandemic. This research uses the study literature review method with a scoping review approach. The literature search is carried out using three databases with predetermined keywords. Get several articles, namely Google Scholar 109 articles, PubMed 540 articles and Proquest 214 articles. After searching for articles by sorting based on the inclusion and exclusion criteria that have been designed, an article assessment is then carried out using the Joanna Briggs Institute (JBI) instrument. The results of the study found several factors that influence social media addiction due to the Covid-19 pandemic including gender, psychological factors there is an impulse to find information related to Covid-19, trauma due to social isolation, depression anxiety and psychological stress due to fear of Covid-19 infection also underlie a person to seek recreation through social media during the pandemic, social factors due to difficulty in interpersonal communication during lockdown, and the purpose and timing of social media use after lockdown was established, resulting in many individuals spending free time inside the home playing social media, as well as causing overuse during the Covid-19 pandemic. The conclusions found show that many of the activities of teenagers carried out online during lockdown resulted in teenagers spending more time with social media, as an escape from personal problems, such as mental stress, stress, and anxiety. So that situations like this cause many teenagers to experience social media addiction as a result of the Covid-19 pandemic. It is hoped that this literature study can be used as an evaluation material and help nurses in dealing with or educating adolescents so that they can avoid social media addiction. Keywords : Academic Stress, Internet Addiction, Students, Online Learning, ABSTRAK Pandemi Covid-19 secara signifikan telah mengubah hampir setiap aspek dalam kehidupan, termasuk aktivitas harian masyarakat seperti sekolah, kerja serta ibadah yang kini harus dilakukan secara daring. Media sosial menjadi salah satu perlengkapan komunikasi yang banyak digunakan di kala pandemi Covid-19. Kondisi ini tidak dipungkiri akan mengakibatkan peningkatan pemakaian media sosial serta membentuk kecanduan media sosial di masa pandemi Covid-19 berlangsung. Penelitian ini bertujuan untuk mengidentifikasi gambaran kecanduan media sosial pada remaja akibat pandemi Covid-19. Penelitian ini menggunakan metode study literature review dengan pendekatan scoping review. Pencarian literature dilakukan dengan menggunakan tiga database dengan kata kunci yang telah ditentukan. Di dapatkan beberapa artikel yaitu Google Scholar 109 artikel, PubMed 540 artikel dan Proquest 214 artikel. Setelah melakukan pencarian artikel dengan menyortir berdasarkan kriteria inklusi dan eksklusi yang sudah dirancang selanjutnya dilakukan penilaian artikel dengan menggunakan instrumen Joanna Briggs Institute (JBI). Hasil telaahan ditemukan beberapa faktor yang mempengaruhi kecanduan media sosial akibat pandemi Covid-19 diantaranya yaitu jenis kelamin, faktor psikologis adanya dorongan untuk mencari informasi terkait Covid-19, trauma akibat isolasi sosial, cemas depresi dan stress psikologi akibat rasa takut terhadap infeksi Covid-19 juga mendasari seseorang untuk mencari rekreasi melalui media sosial selama pandemi, faktor sosial akibat sulitnya komunikasi interpersonal selama lockdown, serta faktor tujuan dan waktu penggunaan sosial media setelah penguncian ditetapkan, mengakibatkan banyak individu menghabiskan waktu luang di dalam rumah dengan bermain media sosial, serta menyebabkan penggunaan yang berlebihan selama pandemi Covid-19. Kesimpulan yang didapatkan menunjukan bahwa banyak aktivitas para remaja yang dilakukan secara online selama penguncian mengakibatkan para remaja lebih banyak menghabiskan waktu dengan media sosial, sebagai pelarian dari masalah pribadi, seperti tekanan mental, stress, dan munculnya rasa cemas. Sehingga situasi seperti inilah yang menyebabkan para remaja banyak mengalami kecanduan media sosial akibat dari adanya pandemi Covid-19. Diharapkan, dengan adanya studi literatur ini dapat menjadi bahan evaluasi dan membantu perawat dalam menangani atau mengedukasi para remaja agar dapat terhindar dari kecanduan media sosial. Kata Kunci: Covid-19, Kecanduan, Media Sosial, Pendemi, Remaja